Evaluation of The Benefits of The Family Hope Program in East Flores Regency - Dominikus Fernandes; David W. Rihi; Jacoba Daud Niga; Alfred O. Ena Mau; Rouwland A. Benyamin (International Journal Labs, 2025)
This study investigates the implementation of the Family Hope Program (PKH) in East Flores Regency, which, despite over a decade of execution, has not yielded significant improvements in poverty reduction, behavioral change, or independence among beneficiary families. The research aims to evaluate the program’s effectiveness across key indicators, including targeting accuracy, service productivity, administrative performance, and resource utilization. Using a qualitative policy evaluation approach, the study collects both primary and secondary data through interviews, observations, and document analysis involving 96 informants. Data were analyzed using Creswell’s spiral analysis technique and assessed via the Discrepancy Evaluation Model. Findings indicate numerous challenges: delayed and misallocated aid, inadequate coordination, insufficient equipment, and irregular monitoring. While PKH has helped reduce short-term financial burdens, it has not yet achieved long-term goals such as empowering recipients or reducing poverty cycles. The study recommends enhancing data accuracy, decentralizing fund distribution, and improving infrastructure and stakeholder coordination. These findings contribute to policy refinements that can increase the relevance, efficiency, and impact of PKH, especially in remote and underserved regions like East Flores.